Seismic analysis and design using the endurance time method. - Estekanchi, Hoymayoon E.; Vafai, Hasssan A. (Momentum Press sustainable structural systems collection., 2018)
"A new approach to seismic assessment of structures called endurance time method (ETM) is developed. ETM is a dynamic analysis procedure in which intensifying dynamic excitations are used as the loading function. ETM provides many unique benefits in seismic assessment and design of structures and is a response history-based procedure. ETM considerably reduces the computational effort needed in typical response history analyses. Conceptual simplicity makes ETM a great tool for preliminary response history analysis of almost any dynamic structural system. Most important areas of application of ETM are in the fields of seismic design optimization, value-based seismic design, and experimental studies. This book is aimed to serve as a coherent source of information for students, engineers, and researchers who want to familiarize themselves with the concepts and put the concepts into practice."--Provided by publisher